Cooperative Learning: General and Theoretical Background - Yassin, Amr Abdullatif; Abdul Razak, Norizan; TG Mohamad Maasum, TG Nor Rizan (Advances in Social Sciences Research Journal, 2018)
This paper provides a general theoretical background for cooperative learning which researchers in this area need to understand before carrying out researchers. The concentration is on both providing a general background and discussing the theories that are related to cooperative learning. The general background includes definitions of cooperative learning, history of cooperative learning, principles of cooperative learning, types of cooperative learning, advantages of cooperative learning, the role of teacher in cooperative learning, and the role of students in cooperative learning. The theoretical background includes Social Interdependence Theory, Comprehensible Input Hypothesis, Zone of Proximal Development, behaviourism, cognitivism and constructivism.